2017
DOI: 10.4049/jimmunol.1602131
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A Dual TLR2 and TLR7 Ligand Induces Highly Potent Humoral and Cell-Mediated Immune Responses

Abstract: TLR agonists are currently being developed and tested as adjuvants in various formulations to optimize the immunogenicity and efficacy of vaccines. The aim of this study was to evaluate the immunostimulatory properties of a novel compound incorporating covalently linked moieties designed to stimulate both TLR2 and TLR7. This dual TLR2/TLR7 agonist induced the maturation of dendritic cells and primed substantial populations of cytolytic and highly polyfunctional effector CD8 T cells in vitro, and safely potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Targeting multiple TLRs has been successfully used in other studies. It was previously shown that a nucleic acid carrier chimeric compound composed of the TLR2 agonist Pam2Cys and the TLR7 agonist CL307 had synergistic immunostimulatory properties compared with the combination of the single TLR agonists in mice (61). Here, we demonstrated that dual TLR2/7 agonists have greater ability to induce the production of soluble factors that reactivate latent HIV than the combination of a single TLR2 and TLR7 agonist (Supplemental Figure 4).…”
Section: Discussionsupporting
confidence: 56%
“…Targeting multiple TLRs has been successfully used in other studies. It was previously shown that a nucleic acid carrier chimeric compound composed of the TLR2 agonist Pam2Cys and the TLR7 agonist CL307 had synergistic immunostimulatory properties compared with the combination of the single TLR agonists in mice (61). Here, we demonstrated that dual TLR2/7 agonists have greater ability to induce the production of soluble factors that reactivate latent HIV than the combination of a single TLR2 and TLR7 agonist (Supplemental Figure 4).…”
Section: Discussionsupporting
confidence: 56%
“…These results are in line with the recently reported study by Gutjahr et al who showed that the structurally very similar dual TLR2/7 ligand PamadiFectin (CL307) induced significantly stronger human DC and cytotoxic T cell responses than the nonconjugated TLR2- and TLR-7 ligands, provided either alone or as a mixture [ 16 ]. In accordance with our own results, application of CL307 resulted in highly enhanced production of antigen-specific IgG2a antibodies against the coapplied HIV antigen p24 [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a mouse B16 melanoma model, intratumoral administration of CL401 and CL413 into established tumors resulted in reduced tumor growth and enhanced survival [ 15 ]. Moreover, after the initial submission of the present manuscript, Gutjahr and coworkers recently published that coapplication of a similar dual TLR2/7 ligand PamadiFectin (CL307) and HIV-1 antigen p24-coated nanoparticles can efficiently boost HIV-specific antibody responses while also inducing a balanced Th1/Th2 profile in mice [ 16 ]. We hypothesized that chemical conjugation of different TLR ligands could be used to create dual TLR2/7 ligands which can promote TLR-mediated Th1-biased immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of T-bet and Eomes was measured using a Transcription Factor Buffer Set (BD Biosciences). Intracellular staining for granzyme B and perforin was compatible with this procedure 28 . Data were acquired using an LSR Fortessa (BD Biosciences) and analyzed with FlowJo software version 9.3.7 (Tree Star Inc.).…”
Section: Methodsmentioning
confidence: 94%